Pelatihan Khutbah Jumat Pada Santri Pondok Pesantren Modern Fatimah Azzikra Paluh Nipah Pematang Cengal Tanjung Pura - Muhammad Ilham; Al Qadri, Muamar (peduli riset dan pengabdian masyarakat, 2024)
The Friday Sermon is a sermon held before the Friday prayer. Fatimah Azzikra Islamic Boarding School is one of the Islamic boarding schools located in II Paluh Nipah hamlet, Pematang Cengal village, Tanjung Pura subdistrict, Langkat district. At this Islamic boarding school, the students have never had any training to learn Friday sermons. In this cottage there is a subject called